2017
DOI: 10.1002/jbm.a.36272
|View full text |Cite
|
Sign up to set email alerts
|

Protein/polysaccharide‐based scaffolds mimicking native extracellular matrix for cardiac tissue engineering applications

Abstract: Tissue engineering has emerged as a viable approach to treat disease or repair damage in tissues and organs. One of the key elements for the success of tissue engineering is the use of a scaffold serving as artificial extracellular matrix (ECM). The ECM hosts the cells and improves their survival, proliferation, and differentiation, enabling the formation of new tissue. Here, we propose the development of a class of protein/polysaccharide-based porous scaffolds for use as ECM substitutes in cardiac tissue engi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
89
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(97 citation statements)
references
References 60 publications
4
89
0
Order By: Relevance
“…To realize the desired 3D cellular processes, numerous 3D biomimetic scaffolds that incorporate different biochemical, mechanical, or architectural cues have been developed for cell cultures [12][13][14][15]. Benefiting from their 3D structural features, these scaffolds have found various applications, such as cell therapy, basic organ physiology, drug discovery, and tissue engineering [16][17][18]. However, because of their polydispersity and the inability to control the degree of connectivity between their pores, most of these scaffolds could only provide limited external surfaces for random cell enrichment and attachment [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…To realize the desired 3D cellular processes, numerous 3D biomimetic scaffolds that incorporate different biochemical, mechanical, or architectural cues have been developed for cell cultures [12][13][14][15]. Benefiting from their 3D structural features, these scaffolds have found various applications, such as cell therapy, basic organ physiology, drug discovery, and tissue engineering [16][17][18]. However, because of their polydispersity and the inability to control the degree of connectivity between their pores, most of these scaffolds could only provide limited external surfaces for random cell enrichment and attachment [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…The nanostructures demonstrated an improvement of biocompatibility, cell proliferation, and neovascularization. Rosellini et al mimicked the chemical composition and molecular interactions found in the native cardiac ECM with scaffolds made of alginate and collagen/gelatin material [121]. The alginate and gelatin scaffolds were superior biochemically and mechanically when compared to alginate and collagen scaffolds.…”
Section: Tissue Regenerationmentioning
confidence: 99%
“…The formation of materials from various polysaccharides has been utilized in tissue engineering, the process of regeneration of damaged tissue or reconstruction of organs by adapting appropriate 3D microenvironments for cell adhesion, proliferation, followed by the formation of new tissues . By using polysaccharides as key components, or as additives, the material scaffolds can mimic parts of the natural extracellular matrices, which are mainly composed of proteoglycans that are long‐chain polysaccharides and fibrous proteins, thus allowing the material to host new cells and improve their survival . Rousseau and Gagnieu used periodate‐oxidized glycogen as a collagen crosslinker to prepare macroscopic films with defined crosslinking degrees for cellular adhesion and proliferation.…”
Section: Glycogen As a Building Block Of Nanostructured Materialsmentioning
confidence: 99%